Mark Twain, his life - Peare, Catherine Owens; Ayer, Margaret (New York, Holt, 1954)
A biography of Samuel Clemens which traces not only the childhood which so greatly influenced his writing, but also his marriage and family life, his travels, and his career as a famous author.
1 8 12 13 33
Keywords: Twain, Mark, -- 1835-1910.; Twain, Mark, -- 1835-1910 -- Biography -- Juvenile literature; Authors, American -- 19th century -- Biography -- Juvenile literature